Missing LINQ: extrusion of a new-generation implantable loop recorder in a child. (20th June 2016) - Chaouki, Ahmad S.; Czosek, Richard J.; Spar, David S.
Abstract: Cardiac rhythm monitoring has been facilitated by the use of implantable loop recorders. New models of these devices are 87% smaller than before allowing for easier implantation and use in the paediatric population. Recommendations are for closure with adhesive. We report a device extrusion in a 6-year-old patient. Based on this, our practice has changed to include subcutaneous sutures this complication.